DAMPAK KEKOSONGAN JABATAN PADA KETUA MAJELIS PEMBINA DAN PENGAWAS DAERAH TERHADAP PENGADUAN ATAS DUGAAN PELANGGARAN PELAKSANAAN JABATAN PEJABAT PEMBUAT AKTA TANAH DI KABUPATEN MAGELANG - Karlesta, Ilham Prakas; Sukisno, Djoko (JOURNAL EQUITABLE, 2024)
The importance of the role of Land Deed Officials (PPAT) in serving the community, especially in terms of the transfer and improvement of land rights and ownership rights to apartment units. In the event of a complaint regarding alleged violations of the implementation of office or code of ethics carried out by PPAT in a region, the injured party can report to the Regional Advisory and Supervisory Council (MPPD) to conduct an examination of the alleged violation of the report. This research is a normative juridical legal research, the method of collecting legal materials used is document study and interviews. The results of the study indicate that the vacancy of the position of the Head of MPPD is administratively an obstacle in the implementation of the duties and functions of MPPD in terms of examining PPAT members reported by the community and alternative efforts to examine the alleged violation of the duties of PPAT Magelang Regency in the midst of the vacancy of the position of the Head of MPPD can be done by consulting with MPPW, issuing policy discretion, and delegation to subordinates.